PENGEMBANGAN MODUL MIKROBIOLOGI BERBASIS INKUIRI TERBIMBING BERDASARKANHASIL PENELITIAN BAKTERI ENDOFIT DARI TUMBUHAN - Mushoffa Mushoffa; Andi Wapa; Agus Wijaksono (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2022)
This research and development aims to develop a valid and effective Microbiology module based guide inquiry on research on Isolation and Identification of Endophytic Bacteria from Ciplukan. The microbiology module was developed in reference to the ADDIE research and development model. The module drafting phase includes:1) the analyzing step through interviews with lecturers and the questionnaire of needs analysis by student respondents; 2) The step of designing learning modules to improve cognitive knowledge and process skills; 3) The step of developing by using module validation; 4) The step of applying which consists of module implementation in learning; 5) The evaluation step which consists of evaluating the validity of modules, cognitive learning outcomes and student science process skills. The results of the study show that the microbiology module developed accordance with the standards of validity, feasibility and practicality.